Determination of trigger levels for groundwater quality in landfills located in historically human-impacted areas. (May 2018) - Stefania, Gennaro A.; Zanotti, Chiara; Bonomi, Tullia; Fumagalli, Letizia; Rotiroti, Marco
Highlights: A method to derive trigger levels for groundwater quality in landfills is presented. This joins data-driven methods (cluster analysis) with soft data (conceptual model). The method is applicable to landfills built on historically human-impacted areas. This allows to distinguish between background and landfill-sourced contamination. Abstract: Landfills are one of the most recurrent sources of groundwater contamination worldwide. In order to limit their impacts on groundwater resources, current environmental regulations impose the adoption of proper measures for the protection of groundwater quality. For instance, in the EU member countries, the calculation of trigger levels for identifying significant adverse environmental effects on groundwater generated by landfills is required by the Landfill Directive 99/31/EC. Although the derivation of trigger levels could be relatively easy when groundwater quality data prior to the construction of a landfill are available, it becomes challenging when these data are missing and landfills are located in areas that are already impacted by historical contamination. This work presents a methodology for calculating trigger levels for groundwater quality in landfills located in areas where historical contaminations have deteriorated groundwater quality prior to their construction. This method is based on multivariate statistical analysis and involves 4 steps: (a) implementation of the conceptual model, (b) landfill monitoring data collection, (c) hydrochemical data clustering and (d) calculation of the trigger levels. The proposed methodology was applied on a case study in northern Italy, where a currently used lined landfill is located downstream of an old unlined landfill and others old unmapped waste deposits. The developed conceptual model stated that groundwater quality deterioration observed downstream of the lined landfill is due to a degrading leachate plume fed by the upgradient unlined landfill. The methodology led to the determination of two trigger levels for COD and NH4 -N, the former for a zone representing the background hydrochemistry (28 and 9 mg/L for COD and NH4 -N, respectively), the latter for the zone impacted by the degrading leachate plume from the upgradient unlined landfill (89 and 83 mg/L for COD and NH4 -N, respectively).